Vitrification of hazardous Fe-Ni wastes into glass-ceramic with fine crystalline structure and elevated exploitation characteristics - Alexander Karamanov, Perica Paunovic, Bogdan Ranguelov, Ejup Ljatifi, Alexandra Kamusheva, Goran Naccevski, Emilia Karamanova, Anita Grozdanov (Elsevier, 2017)
Hazardous residues from ferronickel smelting plant are mixed with glass cullet and are vitrified for 2 h at 1400 oC. The obtained glass is characterized with a very high crystallization trend. As a result, it is inappropriate for sinter-crystallization, but a fine crystalline glass-ceramic can be obtained by bulk crystallization after short heat-treatment at low temperatures. Due to the presence of 1.5 wt.% chromium oxide in the parent glass, together with high amounts of iron oxides and magnesium oxides, the crystallization process is peculiar. It starts during the melt cooling with the precipitation of preliminary Fe-Mg-Cr spinel crystals, which then act as centers for further epitaxial growth of pyroxene phase. It is also highlighted that, due to liquid–liquid immiscibility, the main amorphous phase is characterized by a nonhomogeneous binodal structure, which becomes finer after the nucleation treatment. As a result, pyroxenes with sizes below 1 mm are formed as main crystal phase after the crystallization step. Notwithstanding of the high amount of hazardous wastes in the batch the obtained glass is characterized with high chemical durability. At the same time, the obtained glass-ceramics is characterized by a suitable coefficient of thermal expansion and attractive mechanical characteristics.